A review on non-stereospecific haloalkanoic acid dehalogenases - Tengku Abdul Hamid, Tengku Haziyamin; Abdul Hamid, Azzmer Azzar; Huyop, Huyop (Academic Journals, 2011)
Haloalkanoic acid dehalogenases remove halides from organic haloacids and have potential as bioremediation agents. DehE from Rhizobium sp. RC1, DehI from Pseudomonas putida PP3 and D,LDEX 113 from Pseudomonas sp. 113 are non-stereospecific dehalogenases that invert the configurations of D- and L- carbons bound to a halogen. The kinetics of DehE has been partially characterized and brominated compounds have greater specificity constant values than do the corresponding chlorinated compounds. The sequence of DehE is similar to that of DehI; therefore, the two enzymes may have similar structures and functions. The three-dimensional structure of DehI is known and its reaction mechanism was inferred from its structure and a mutagenesis study of D,L-DEX 113. Aspartate residues at positions 189 and 194 in DehI and D,L-DEX 113 were predicted to be involved in catalysis. These residues activate a water molecule that directly attacks the chiral carbon. Because DehE and DehI are sequentially related, delineating the structure of DehE is important to ascertain if the catalytic residues and reaction mechanism are the same for both enzymes. A structural prediction, sequence-homology modeling and a site-directed mutagenesis study of DehE might help achieve this goal.